Barriers to early identification of autism in Brazil - Sabrina H. Ribeiro; Cristiane S. de Paula; Daniela Bordini; Jair J. Mari; Sheila C. Caetano (Brazilian Journal of Psychiatry, 2017)
Objective: Parents of children with autism spectrum disorders (ASD) seem to perceive that their child’s development is not following the normal pattern as early as the first year of life. However, ASD children may not receive a diagnosis until they are of preschool age, especially in low- and middle-income countries. The objective of this study was to evaluate the pathway between initial parental concerns about atypical child development and ASD diagnosis in Brazil. Methods: Nineteen mothers whose children had been diagnosed with ASD participated and were interviewed. The ASD group consisted of two girls and 17 boys, with a mean age of 93.0 months (SD 48.4 months; range 39-197 months). Results: Mothers had their first concerns regarding ASD when children were 23.6±11.6 months old, but formal diagnosis occurred at a mean ± SD age of 59.6±40.5 months, corresponding to a 3-year delay. Most mothers felt discouraged to address their concerns due to negative experiences with health professionals. Conclusion: In Brazil, mothers perceived the first signs of ASD in their children at an age similar to that reported in other countries, but the diagnosis of ASD seemed to be delayed. Consistent with the literature, mothers reported negative experiences with health professionals during the pathway to achieving ASD diagnosis.